Equality at the Polls: Female Representation Challenges in Musi Banyuasin Regency in 2019-2024 - Utami, Nezi; Budianto, Kun; Harahap, Raegen (Ampera: A Research Journal on Politics and Islamic Civilization, 2024)
In Musi Banyuasin Regency, the quest for gender equality in political representation faces multifaceted challenges. This study explores the barriers hindering female participation and representation in local electoral processes. Through qualitative analysis, interviews with key stakeholders including female candidates, local officials, and community leaders were conducted to uncover underlying issues.The findings reveal several critical challenges. Firstly, structural barriers such as entrenched patriarchal norms and limited access to financial resources significantly impede women from contesting elections on an equal footing with their male counterparts. Secondly, despite legal frameworks promoting gender equality, cultural perceptions and societal expectations often undermine women’s political ambitions. Thirdly, the role of political parties emerges as pivotal, with varying levels of support and nomination opportunities affecting women’s candidacy viability. Moreover, the study highlights community attitudes towards female leadership, where biases and stereotypes persist, shaping voter preferences and electoral outcomes. These dynamics perpetuate a cycle of underrepresentation and marginalization of women in decision-making bodies like the local legislative council. Ultimately, achieving gender equality at the polls in Musi Banyuasin Regency necessitates concerted efforts from various stakeholders to dismantle barriers, reshape cultural narratives, and advance inclusive governance practices